Isolation and characterisation of carbapenem-resistant Pseudomonas aeruginosa from hospital environments in tertiary care hospitals in Dhaka, Bangladesh. (September 2022) - Saha, Karabi; Kabir, Nayel Daneesh; Islam, Md. Rayhanul; Amin, Mohammed Badrul; Hoque, Kazi Injamamul; Halder, Kakali; Saleh, Ahmed Abu; Parvez, Md. Anowar Khasru; Begum, Khurshida; Alam, M. Jahangir; Islam, Mohammad Aminul
ABSTRACT: Objectives: Increasing evidence of carbapenem-resistant Pseudomonas aeruginosa (CRPA) infection in healthcare facilities poses an alarming threat to public health. There is little evidence on the occurrence of this organism in Bangladeshi hospitals. Methods: We collected 117 environmental swab samples from two tertiary care hospitals in Dhaka, Bangladesh and tested for Pseudomonas species by nonselective enrichment of swabs followed by plating on Cetrimide agar. We confirmed the isolates as P. aeruginosa by API 20NE test and polymerase chain reaction Polymerase Chain Reaction (PCR) for 16S rRNA gene. We analysed P. aeruginosa isolates for susceptibility against 15 clinically important antibiotics and tested the carbapenem-resistant isolates for metallo β-lactamase (MBL). All CRPA isolates were characterised for carbapenem-resistant genes, virulence genes and biofilm formation genes. Results: Of 117 swab samples, 82 (70%) were tested positive for P. aeruginosa . All P. aeruginosa isolates were multidrug-resistant, and 39% (n = 32) of isolates were CRPA. Around 56% (n = 18) of CRPA were MBL-producing; 22% (n = 7) of isolates were positive for carbapenemase gene bla NDM followed by 16% (n = 5) for bla VIM and 13% (n = 4) for bla IMP . Sequencing identified these genes as bla NDM-1, bla IMP-13, bla VIM-2 variants. Based on optical density values, 94% (n = 30) of CRPA isolates were capable of producing biofilms. All CRPA isolates (n = 32) were positive for at least 1 of 6 biofilm-associated genes and 4 of 12 virulence genes tested in the study. Conclusion: Hospital environments in Bangladesh are contaminated with highly virulent CRPA, which might be a potential source of hospital-acquired infections, accentuating the need for strengthening hospital infection control programs.